Basics and Directions of Tourism Development in Uzbekistan - Khidiraliyev Komil Esanovich; Jorayev Adkham Mengziya (Scientific Trends, 2024)
This article analyzes specific aspects of the tourism industry in detail. Also, on the basis of the state program, the fundamentals and directions of tourism development in Uzbekistan were studied. The mechanisms for the future natural, social and economic development of the tourism industry of Uzbekistan are presented.
Keywords: Tourism, industry, object, basics, directions, infrastructure, hotel, sustainable development, program.